Agrobactrium tumefaciens mediated genetic transformation in Kudangal (centella asiatica L. urban) - Nanditha Krishnan V (Department of Plant Biotechnology, College of Agriculture, 2006)
A study on “Agrobacterium tumefaciens mediated genetic transformation in kudangal (Centella asiatica L. Urban.)” was conducted at the Department of Plant Biotechnology, College of Agriculture, Vellayani during 2004-2006.